(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2025)
This study presents an innovative and eco-friendly process using peracetic acid (PAA) for lignocellulosic fibres viz.,banana, flax, jute and ramie at lower temperatures (70-76 ℃) and pH conditions (7-8). Bleaching of these fibres with different proportions of cellulose, hemicellulose and lignin is carried out using optimised recipe for the individual fibres using statistical design. After bleaching, the whiteness index (WI) of all the fibres significantly improves with maximum retention of fibre strength (75 – 83 %). To make the process sustainable, the remnant PAA bleach bath is reclaimed twice for bleaching scoured fibres. Results show that the left-out liquor can be reused effectively twice to produce semi-bleached (WI: 64.5 - 69.1) to quarter-bleached (WI: 54.2 - 64.1) fibres, which may be dyed in medium to darker shades. The concentration of PAA in the bath is gradually depleted in the successive bleach baths, resulting in maximum utilisation of PAA. The discharged bleach liquor is assessed for total dissolved solids, turbidity, chemical oxygen demand, pH, electrical conductivity and residual PAA, keeping in mind the sustainability of the process.